2002
DOI: 10.1103/physreve.66.056118
|View full text |Cite
|
Sign up to set email alerts
|

Coevolutionary games on networks

Abstract: We study agents on a network playing an iterated Prisoner's dilemma against their neighbors. The resulting spatially extended co-evolutionary game exhibits stationary states which are Nash equilibria. After perturbation of these equilibria, avalanches of mutations reestablish a stationary state. Scale-free avalanche distributions are observed that are in accordance with calculations from the Nash equilibria and a confined branching process. The transition from subcritical to critical avalanche dynamics can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
187
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(187 citation statements)
references
References 34 publications
0
187
0
Order By: Relevance
“…There is much current interest to study evolutionary game dynamics on graphs, which also leads to non-uniform interaction rates. [Ellison, 1993, Nakamaru et al, 1997& 1998, Epstein, 1998, Abramson & Kuperman, 2001, Ebel & Bornholdt, 2002, Szabo & Vukov, 2004, Ifti & et al, 2004, Nakamaru & Iwasa, 2005, Lieberman et al, 2005 The fundamental Lotka-Volterra equation of ecology is equivalent to the replicator equation of evolutionary game theory [Hofbauer & Sigmund, 2003].…”
Section: Resultsmentioning
confidence: 99%
“…There is much current interest to study evolutionary game dynamics on graphs, which also leads to non-uniform interaction rates. [Ellison, 1993, Nakamaru et al, 1997& 1998, Epstein, 1998, Abramson & Kuperman, 2001, Ebel & Bornholdt, 2002, Szabo & Vukov, 2004, Ifti & et al, 2004, Nakamaru & Iwasa, 2005, Lieberman et al, 2005 The fundamental Lotka-Volterra equation of ecology is equivalent to the replicator equation of evolutionary game theory [Hofbauer & Sigmund, 2003].…”
Section: Resultsmentioning
confidence: 99%
“…In all these cases, however, individuals cannot influence how often they will interact and how long particular interactions will last. On the other hand, other studies have explored the possibility of individuals meeting assortatively, by means of selective partner choice (Eshel and Cavalli-Sforza, 1982;Noë and Hammerstein, 1994;Skyrms and Pemantle, 2000;Bala and Goyal, 2001;Ebel and Bornholdt, 2002;Eguiluz et al, 2005;Biely et al, 2005) or by means of volunteering participation (Peck and Feld-man, 1986;Hauert et al, 2002;Szabó and Hauert, 2002;Hauert and Szabó, 2003;Aktipis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the seminal paper introducing games on grids [18], evolutionary games on graphs and complex networks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have proven instrumental in raising the awareness of the fact that relaxing the simplification of well-mixed interactions may lead to qualitatively different results that are due to pattern formation and intricate organization of the competing strategies, which reveals itself in most unexpected ways. Specifically for the spatial public goods game [38,39], it has recently been shown that inhomogeneous player activities [40], appropriate partner selection [41,42], diversity [43][44][45], the critical mass [46], heterogeneous wealth distributions [47], the introduction of punishment [48,49] and reward [50], as well as both the joker [51] and the Matthew effect [52], can all substantially promote the evolution of public cooperation.…”
Section: Introductionmentioning
confidence: 99%